DDiscourse of transformation in organisational change management / Christiantine Della a/p Anthony Pitchay - Anthony Pitchay, Christiantine Della (2011)
This study examines the discursive construction of ideological change and identity within the practice of organisational control in organisational change management. The focus of the study was to examine how the organisation through its large-scale reengineering process to implement organisational change initiatives appropriated discourse of transformation to effect change among its organisational members. Reengineering is defined as the process of reorganising, restructuring, and redesigning work processes and job functions to bring about breakthrough improvements in performance. The organisation’s focus is to change mindsets and persuade members to embrace characteristics, traits, attitudes and behaviour that are deemed to be beneficial to the organisation. The management of the organisation attempts to align or realign its organisational members to change their ways of thinking and embrace change. The practice of managerial action to unobtrusively develop appropriate member identity implicates organisational control. Control is a central organisational function. It is a means by which activities and resources are coordinated and directed towards the achievement of an organisation’s goals. The study examines this organisational control from the lens of ideological and identity construction in the discourse of an institution undergoing organisational change. The objective of the study is to discover how discourse of transformation is used as an object of discursive construction of reality in the construction of an ‘ideal’ member identity and ideological change or change in mindsets, the strategies used to accomplish this, and how this serves the objective of organisational control. The theoretical framework for the study is informed by theories of identity and ideology in discourse, theories of power and language as articulated in the field of critical discourse analysis. The data consist of transcripts of nine ‘Sharing Sessions’, ten articles from the organisation’s newsletters and memoranda from the Human Resource Department of the organisation. The method of analysis used is critical discourse analysis that takes into account textual and contextual analysis. The analytical framework for textual analysis shows how identity and the construction of ideology may be located and analysed in texts from a grammatically oriented analysis, the use of rhetorical strategies, intertextual as well as action oriented analysis. The analysis shows that discourse of transformation is appropriated to change mindsets and persuade members to embrace characteristics, traits, attitudes and behavior that are deemed to be beneficial to the organisation. The findings indicate how the discourse constructs an identifiable ideology and member identity that is offered as the ‘ideal’. The change in mindset and ‘ideal’ member identity is a means by which the organisation inculcates a self-disciplining or ‘obedient’ membership where members are influenced to adopt change management initiatives that are prescribed by the management. The construction of ideological change and ‘ideal’ member identity involves the subtle and skillful use of a variety of linguistic resources and discourse strategies. The use of these discourse strategies conscripts members to embrace what is shared and articulated through the ‘Sharing Sessions’ as well as the articles and memoranda which are disseminated. Members are influenced to adapt and embrace change and adopt what is desirable or appropriate through the discourse.